Analysis of the Effect of Structural Empowerment on Motivation and Performance of Nurses in Quality Patient Safety - Sukmono, Ramang; Lestari, Indah; Rahmawati, Ima; Saudah, Noer; Maryam, Dewi; Zamroni, Asroful Hulam (Indonesian Journal of Global Health Research, 2024)
The problem of patient safety quality is considered less than optimal in health services which is caused by inadequate organizational infrastructure, leadership effectiveness, job characteristics, and structural empowerment which includes the motivation of nurses as fundamental health workers. Therefore, this study aims to analyze the effect of structural empowerment on nurses' motivation and performance in the quality of patient safety. Method: This research used a cross-section design with 116 respondents. The sample was selected using a cluster random sampling technique. Data collection using a questionnaire includes the independent variable in the form of structural empowerment and the dependent variable in the form of work motivation and nurse performance in patient safety quality with all questionnaire a valid value of r = 0.714-0.942 and Cronbach alpha reliability 0.982. Data were analyzed using the logistic regression test with a p-value ≤ 0.05. Results: The research results show that structural empowerment has a positive and unidirectional influence on work motivation (0.000) and nurse performance in patient safety quality (0.016). Conclusion: Structural empowerment provides implementing nurses with access and freedom to leaders including opportunities, information, support, resources, formal power, and informal power. Structural empowerment gives implementing nurses a feeling of comfort in their work so that they are more motivated and improve nurses' performance in terms of patient safety quality.